Decomposition of spent radioactive ion‐exchange resin using photo‐Fenton process. Issue 9 (7th May 2020) - Feng, Wendong; Wang, Yunhai; Li, Jian; Gao, Kai; An, Hongxiang
Abstract: BACKGROUND: The treatment of spent radioactive ion‐exchange resin is of great importance in reducing total waste volume and minimizing potential environmental hazards. In this study, a comparative investigation of resin decomposition by the Fenton and photo‐Fenton process was performed to address these concerns. RESULTS: The effect of UV energy density and irradiation time on residue chemical oxygen demand (COD) was investigated. With a UV energy density of 6.1 J cm −2 and irradiation time of 120 min, the COD removal ratio reached 97.3%. Under optimized conditions, the residue COD obtained via photo‐Fenton was 47.3% lower than that via Fenton. Scanning electron microscopy (SEM), Fourier transform infrared (FTIR) and ion chromatography (IC) were used to characterize the resin beads and intermediates. Four types of small molecular organic acids were monitored during the reaction. The degradation process of two stages was proposed, involving resin dissolution and mineralization. CONCLUSION: Photo‐Fenton showed better performance for IRN 77 resin degradation compared to the Fenton process. Both the UV energy density and irradiation time showed significant effects on resin degradation. UV irradiation enhanced the mineralization stage during resin degradation. Oxalic acids showed the highest concentration in all main intermediates. © 2020 Society of Chemical Industry